2016
DOI: 10.1016/j.ejps.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Towards a test to predict 5-fluorouracil toxicity: Pharmacokinetic data for thymine and two sequential metabolites following oral thymine administration to healthy adult males

Abstract: a test to predict 5-fluorouracil toxicity: Pharmacokinetic data for thymine and two sequential metabolites following oral thymine administration to healthy adult males, (2015), doi: 10.1016/j.ejps.2015.10.001 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The values for the 0–4 h‐urinary THY/DHT ratios in the current study were comparable to the range reported previously in healthy volunteers and also in the previous case series . We observed a non‐normal distribution of urinary THY/DHT ratios, with a remarkably high number of patients in the cohort (48%) with elevated ratios (THY/DHT > 4).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The values for the 0–4 h‐urinary THY/DHT ratios in the current study were comparable to the range reported previously in healthy volunteers and also in the previous case series . We observed a non‐normal distribution of urinary THY/DHT ratios, with a remarkably high number of patients in the cohort (48%) with elevated ratios (THY/DHT > 4).…”
Section: Discussionsupporting
confidence: 90%
“…Our earlier work assessing the THY challenge test focussed on the plasma pharmacokinetics of THY and its catabolites in healthy participants and in a group of 6 patients who had previously experienced G3–4 fluoropyrimidine toxicity . Intensive serial blood sampling was required to detect individuals with aberrant THY pharmacokinetic disposition (either the ETA phenotype or decreased metabolic clearance).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5-FU is an analog of uracil that operates as an anti-metabolite by inhibiting thymidylate synthase [ 29 ] and is a widely used chemotherapeutic agent for colorectal cancer. However adverse effects including life-threatening mucositis or bone marrow suppression occur in approximately 11 % of patients on infusion therapy and 25 % with bolus therapy [ 30 ]. In our CT26 tumor-bearing murine model, we imitated the clinical chemotherapy schedule for the cycles and examined the immune functions after one- and three-cycle treatment rather than only final evaluation of immune status after chemotherapy [ 6 , 8 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study found that the relative level of dihydrothymine in the pyrimidine metabolic pathway was significantly decreased in students with depression. Dihydrothymine is a marker of thymine synthesis and metabolism that is often used to evaluate the metabolic level of thymine [49]. As a basic base unit of DNA and RNA, thymine plays an important physiological role in skin cancer caused by ultraviolet injury and in other diseases [50].…”
mentioning
confidence: 99%